Generation of human islet-specific regulatory T cells by TCR gene transfer. (May 2017) - Hull, Caroline M.; Nickolay, Lauren E.; Estorninho, Megan; Richardson, Max W.; Riley, James L.; Peakman, Mark; Maher, John; Tree, Timothy I.M.
Abstract: Based on the success in animal models of type 1 diabetes (T1D), clinical trials of adoptive regulatory T cell (Treg) therapy are underway using ex vivo expanded polyclonal Tregs. However, pre-clinical data also demonstrate that islet-specific Tregs are more potent than polyclonal Tregs at reversing T1D. Translation of this approach into man will require methods to generate large populations of islet-specific Tregs which, to date, has proved to be a major hurdle. Here we demonstrate the feasibility of lentiviral-mediated T cell receptor (TCR) gene transfer to confer antigen specificity on polyclonal human Tregs. Targeting has been achieved using TCRs isolated from human islet-specific and viral-specific CD4 + T cell clones. Engineered T cells demonstrated expression of ectopically-delivered TCRs, resulting in endowment of cognate antigen-specific responses. This enabled antigen-specific suppression at increased potency compared to polyclonal Tregs. However, cells transduced with islet-specific TCRs were less responsive to cognate antigen than viral-specific TCRs, and in some cases, required additional methods to isolate functional antigen-specific Tregs. This study demonstrates the potential of TCR gene transfer to develop islet-specific Treg therapies for effective treatment of T1D, but also highlights that additional optimisation may be required to achieve its full potential. Highlights: Polyclonal Treg transfer has reached the clinic as a therapy for type 1 diabetes. Mouse models show that antigen specific Tregs may be a more effective therapy. Lentiviral TCR gene transfer can redirect the specificity of polyclonal Tregs. This approach can be used to generate large numbers of islet specific Tregs. Islet specific Tregs were capable of mediating antigen specific suppression.